DAMPAK LITERASI KEUANGAN SYARIAH DAN AKSESIBILITAS DIGITAL TERHADAP INKLUSI PERBANKAN SYARIAH CIAMIS - Acim Acim; Akmaludin Akmaludin; Ihrom Jaelani (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2026)
This study aims to analyze and empirically test the effect of Islamic financial literacy and digital service accessibility, both partially and simultaneously, on Islamic banking financial inclusion among the community in Ciamis Regency. The research approach used is quantitative with a causal associative method. Since the exact population size is unknown, the minimum sample size was determined using the Cochran formula, which was then rounded to 100 respondents using a purposive sampling technique. Primary data collection was conducted through the distribution of a structured Likert-scale questionnaire. The collected data were analyzed using classical assumption tests, multiple linear regression analysis, and hypothesis testing with the assistance of IBM SPSS software. The results showed that partially, Islamic financial literacy had a positive and significant effect on Islamic banking financial inclusion (t = 2.702; sig = 0.008). Similarly, digital service accessibility proved to have a partial positive and highly dominant significant effect (t = 11.461; sig = 0.000). Simultaneously, both variables significantly influenced Islamic banking financial inclusion in Ciamis Regency (F = 96.330; sig = 0.000). The R Square value of 0.665 indicates that the combined cognitive contribution of Islamic financial literacy and digital accessibility infrastructure in explaining variations in Islamic banking financial inclusion is 66.5%, while the remaining 33.5% is explained by other variables outside this research model. The conclusion of this study confirms that expanding Islamic banking financial inclusion in semi-urban areas requires an absolute balance between strengthening the spiritual values of Islamic finance and providing reliable digital technology infrastructure.